SmKFB5 protein regulates phenolic acid biosynthesis by controlling the degradation of phenylalanine ammonia-lyase in Salvia miltiorrhiza - Yu, Haizheng (Journal of experimental botany, 2021)
© The Author(s) 2021. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.